Analisis Dampak Penggunaaan Aplikasi Tiktok Terhadap Minat Beli Mahasiswa Prodi Manajemen Universitas Buana Perjuangan Karawang Angkatan 2020 - Cutisah Cutisah; Sungkono Sungkono (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The tiktok application is a social media that has been widely used by Indonesian people, including students of the Management Study Program, Faculty of Economics and Business, Buana Perjuangan University, Karawang class of 2020. As students who both use the tiktok application, of course, they have heard of the phenomena that occur in this application, because a content that is posted on the tiktok application is very fast viral. The features in the tiktok application can be used to market a product such as in E-commerce and also content about products that are currently viral on fyp tiktok can influence buying interest among students. The purpose of this study is to determine the impact of using the tiktok application on buying interest in Management Study Program students at Buana Perjuangan Karawang University Class of 2020. This research uses a qualitative method with a descriptive approach. This research study focuses on how the impact caused by the use of the Tiktok application on the buying interest of students of the Management Study Program, Faculty of Economics and Business, Buana Perjuangan University, Karawang Class of 2020. The results showed that there were positive and negative impacts from using the tiktok application on student buying interest , the positive impact is that it is easy for students to find information about products, can buy products at lower prices because of promos on tiktok live streaming. The negative impact that is caused is the emergence of consumptive behavior because spending money without careful consideration.